Prevalencia de anemia ferropénica en los niños del primero al cuarto año de Educación Básica de la escuela matutina Cuarto Centenario. - Quizhpe Agreda, Juan Carlos (2009)
The present study is of descriptive character whose objective was to determine the Prevalence of Anemia Ferropénica in the Children from the First one to the Fourth Year of Basic Education of the School Morning Fourth Centennial of the city of Loja, during the period October 2006 to March 2007. The tests were carried out in a sample of 100 scholars of the masculine sex, understood among 5 to 9 years of age to who you/they were carried out exams to determine the hemoglobin, iron sérico, transferrina and transferrina saturation. After having carried out the study of hemoglobin dosage it was observed that 33 children (33%) they presented low values of hemoglobin (whose value fluctuates among 10,22 to 11,95 g/dl), and 14 children (42,4%) they have low values of iron sérico being this value among 51 to 60 ug/dl, with respect to the transferrina and the transferrina saturation these were presented inside the normal values. In accordance with the obtained results can say that 14% of the children in study presumptive of anemia ferropénica is affected. These obtained values will be of great support for the I diagnose doctor.